Evaluating a novel sign's impact on whether park visitors enter a dangerous river - Deborah C. Girasek (BMC, 2019)
Abstract Background Between 1972 and 2015, 56 visitors to the two national parks that border the Potomac River Gorge experienced fatal drowning. In 2016, the George Washington Memorial Parkway (GWMP), and the Chesapeake and Ohio National Historical Park (CHOH) partnered with a researcher to see if enhancement of their risk communication strategies could reduce behaviors that contribute to these deaths. Methods An experimental sign, which informed visitors that water entry was illegal and could result in a fine exceeding $200 was developed, and displayed on alternating weekend days from July 30 to September 11, 2016. Those signs were displayed at each park's entrance, on restroom doors, at trailheads, and at both shorelines of the Potomac. At other times the experimental signs were covered, but a standard safety sign was always present. Cameras were used to record water entries. Results Cameras captured 1441 images. Approximately 2% of the images in CHOH and 1% of the images in GWMP showed a visitor in the water. Our multivariate analysis revealed that air temperature, beach count, and sign condition were significantly associated with water entry. When our experimental sign was displayed, the odds of an image showing someone in the water was reduced by 63%. Conclusions A sign alerting park visitors to the fact that water entry is illegal, and could potentially result in a considerable fine, was associated with significantly reduced risk-taking. While intuitive, this finding is a reminder to consider whether warnings that focus on non-health consequences might be more salient to at-risk populations.